APLIKASI GOOGLE CLASSROOM SEBAGAI MEDIA MENGIRIMKAN TUGAS SISWA SELAMA PANDEMI COVID-19 - Teguh Prasetyo; Futeri Maharani Suradi; Via Damayanti; Meriyati (Jurnal Penjaminan Mutu, 2022)
This study aims to describe an implementation of learning that has been carried out in elementary schools in Purwasari 2 West Java Province since 2020 has implemented a google classroom application as a learning innovation for student learning activities. This case becomes a phenomenon because google classroom is very supportive. After all, the teacher can provide learning material on the page that has been prepared and functioning to collect student assignments. This is followed by using learning variations such as video call applications, zoom meetings, and quizizz. Although it can be concluded that google class learning is carried out in a good category in Purwasari 2 elementary school to send student task media, making it easier for teacher archiving if needed. However, schools face obstacles, namely the impact of saturation for teachers and students and internet quota assistance. There needs to be a more frequent training program to become a place for teachers to develop the ability to use technology in learning supported by supporting facilities and infrastructure, such as the application of google classroom. On the other hand, there is a need for further socialization for parents to accompany children to learn online through the google classroom application.